2020
DOI: 10.3390/ijms21249736
|View full text |Cite
|
Sign up to set email alerts
|

Development and Maintenance of Epidermal Stem Cells in Skin Adnexa

Abstract: The skin surface is modified by numerous appendages. These structures arise from epithelial stem cells (SCs) through the induction of epidermal placodes as a result of local signalling interplay with mesenchymal cells based on the Wnt–(Dkk4)–Eda–Shh cascade. Slight modifications of the cascade, with the participation of antagonistic signalling, decide whether multipotent epidermal SCs develop in interfollicular epidermis, scales, hair/feather follicles, nails or skin glands. This review describes the roles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…The skin regulates body temperature, provides immune defense, and prevents pathogen invasion 57,66 . Different stem cells exist in the skin and skin appendages 67 and exhibit strong regeneration potential under damage to the skin. Skin photoaging is characterized by a decrease in the activity and number of epidermal stem cells (EPCs) 68 .…”
Section: Stem Cell Therapy For Skin Rejuvenationmentioning
confidence: 99%
“…The skin regulates body temperature, provides immune defense, and prevents pathogen invasion 57,66 . Different stem cells exist in the skin and skin appendages 67 and exhibit strong regeneration potential under damage to the skin. Skin photoaging is characterized by a decrease in the activity and number of epidermal stem cells (EPCs) 68 .…”
Section: Stem Cell Therapy For Skin Rejuvenationmentioning
confidence: 99%
“…According to previous studies, a complex regulatory mechanism involving multiple genes and pathways underlies hair placode formation ( Duverger and Morasso, 2009 ; Schneider et al, 2009 ; Sennett and Rendl, 2012 ). Besides lncRNA627.1/miR-29a-5p/EDAR, we also identified other DE mRNAs at E41, such as BMP3 ( Nie et al, 2018 ), DKK4 ( Mokry and Pisal, 2020 ), FGFR2 ( Nguyen et al, 2018 ) , and FRZB ( Hu et al, 2020 ), which participate in hair placode formation via the Wnt/β-catenin, BMP and FGF signaling pathways ( Supplementary Table S2 ). Although excluded from ceRNA construction, these were differentially expressed between normal and hairless pigs at E41, suggesting these genes may exert a synergistic effect on hair placode formation via other regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Stem cells expressing Blimp1 or CD34 are predominantly located in the isthmus and bulge regions. 9,13,14 Immunohistochemical staining demonstrated that the expression of CD34, p63, LGR6 and LGR5 significantly decreased in atrophic acne scar compared to normal skin (Figure 2b). The expression of CK15 and Blimp1 also tended to decrease, however the difference was not statistically significant (p = 0.077 for CK15 and p = 0.236 for Blimp1).…”
Section: Expression Of Stem Cell Markers Is Reduced In the Interfolli...mentioning
confidence: 99%